Use of Cell Envelope Targeting Antibiotics and Antimicrobial Agents as a Powerful Tool to Select for Lactic Acid Bacteria Strains With Improved Texturizing Ability in Milk Fermentations - Sørensen, Kim I.; Kjærbølling, Inge; Neves, Ana Rute; Machielsen, Ronnie; Johansen, Eric (Frontiers in Bioengineering and Biotechnology, 2021)
Many antibiotics and antimicrobial agents have the bacterial cell envelope as their primary target, interfering with functions such as synthesis of peptidoglycan, membrane stability and permeability, and attachment of surface components. The cell envelope is the outermost barrier of the bacterial cell, conferring protection against environmental stresses, and maintaining structural integrity and stability of the growing cell, while still allowing for required metabolism. In this work, inhibitory concentrations of several different cell envelope targeting antibiotics and antimicrobial agents were used to select for derivatives of lactic acid bacteria (LAB) with improved properties for dairy applications. Interestingly, we observed that for several LAB species a fraction of the isolates had improved milk texturizing capabilities. To further improve our understanding of the mechanisms underlying the improved rheology and to validate the efficacy of this method for strain improvement, genetic and physiological characterization of several improved derivatives was performed. The results showed that the identified genetic changes are diverse and affect also other cellular functions than the targeted cell surface. In short, this study describes a new versatile and powerful toolbox based on targeting of the cell envelope to select for LAB derivatives with improved phenotypic traits for dairy applications.